COVID-19 Pandemic and Export: Evidence from Lithuania - Petrylė, Vaiva (Organizations and Markets in Emerging Economies, 2022)
In this paper I apply the gravity model to analyse structural changes of Lithuania’s export during the first pandemic year. Lithuania was selected as a case of a small open economy with relatively high numbers of Covid-19 cases, on one hand, and a rather small decrease of its GDP growth in 2020, on the other. The research aims to fill the gap in the current literature by investigating heterogeneity in the goods export in terms of both product groups and export destinations. I also analyse whether the importance of distance and other export determining factors changed during the pandemic year. Results suggest that Lithuania’s export is resilient to economic shocks. Although the effects of Covid-19 were heterogeneous, the pandemic year had only a negligible impact on Lithuania’s export structure. The influence of distance or other export determinants on Lithuania’s export structure did not change during 2020.
Keywords: COVID-19; international trade; export; gravity model; Lithuania